Fabrication and characterization of l-ascorbyl palmitate and phospholipid-based hybrid liposomes and their impacts on the stability of loaded hydrophobic polyphenols. (1st January 2023) - Chen, Mianhong; Li, Ruyi; Lu, Xuli; Dai, Yaping; Chen, Tinghui; Xing, Yuhang; Xue, Lu; Duan, Zhihao; Zhou, Wei; Li, Jihua
Highlights: l -Ascorbate palmitate (LAP) incorporated liposome was produced by simple hydration and microfluidization. LAP increased the surface negative charges, antioxidant capacity, rigidity and orderliness of liposomes. High LAP incorporated ratio could decrease the encapsulation ability of the control liposome. The storage stability of hydrophobic polyphenol in liposomes could be improved by LAP. Abstract: The aim of this study was to evaluate the influence of l -ascorbyl palmitate (LAP) as an additive to liposome formulations by self-assembling with soy lecithin to form hybrid liposomes, in order to enhance the physical stability and bioactivator-loaded retention ratio of the LAP incorporated liposomes (LAP-LP). The addition of LAP significantly increased its surface negative charge and strong hydrophobic interactions occurred between the hydrophobic tails of LAP and phospholipids resulting in more compactly ordered, rigid and hydrophobic phospholipid bilayers as indicated by surface tension, fluorescence probes and DSC. These changes enhanced the stability of hydrophobic polyphenol loaded LAP-LP during storage. Particularly, after four weeks storage at 37 °C for naringenin loaded liposomes, the retention ratio of pure liposome decreased dramatically to 12.5 %, while the LAP-LP remained above 74.5 %. This study opens up the potential for the LAP-LP to be developed as a food-grade multifunctional formulation for encapsulating and delivering bioactivators.